35 TW pulse generation for laser-plasma interaction studies - Pepler, D; Danson, C; Barr, J; Barzanti, L; Ebbage, MD; Edwards, C; Gander, M; Hanna, D; Hughes, D; Hutchinson, M; Key, M; Majdabadi, A; et al. (IEEE, 1994)
We report the development at the VULCAN Nd:glass laser at the Rutherford Appleton Laboratory of chirped pulse amplification (CPA) operation at 620 fs to give 35 TW in a single large aperture beam, with focused intensities on target in excess of 1019 Wcm-2. We present a technique to optimise the parallelism of the compression gratings, whereby two CW alignment beams at wavelengths of 1053 nm and 1064 nm were injected into the compressor.